Structures of Cytoskeleton and Disease Interactions - Abdullah Melekoğlu; Oğuz Karahan (Acta Medica Alanya, 2019)
Researchers reported different basics for different kind of diseases with advanced technology. Meanwhile, investigators are focused on to clarify the interactions of basic cellular mechanisms recently. Therefore, cytoskeletal researches are gain importance due to this tendency. The cytoskeletal structures are responsible for interconnects between cell nucleus, cytoplasm and also extracellular matrix, whereby it creates a communication link between cellular molecules and signalization transport. The cytoskeleton is constructed from three kinds of protein filaments as: actin filaments, intermediate filaments, and microtubules. The nature of these structures is briefly outlined and the literature review that is reporting the relationship between cytoskeleton components and common disorders is presented in this paper.